Imagining the Future. - Yan, Lu (Beijing Review, 2025)
The article focuses on the significant growth and development of China's science fiction (sci-fi) industry, which reached a total revenue of nearly 109 billion yuan ($15 billion) in 2024. Key areas of growth include literature, films and TV shows, video games, derivative products, and themed tourism, with notable contributions from acclaimed authors like Liu Cixin and Hai Ya. The report from the China Sci-Fi Research Center highlights the integration of advanced technologies such as artificial intelligence (AI) and virtual reality (VR) in content creation, which is expected to drive further innovation and economic growth in the sector. Additionally, initiatives in cities like Beijing aim to enhance the sci-fi ecosystem, showcasing the potential of sci-fi to reflect and inspire technological advancements in China.